Education About Early Detection Of Emergencies In Patients With Catastropic Diseases Through Early Warning Score - Hasanah, Nisa El (JURNAL PENGMAS KESTRA (JPK), 2024)
Early detection of emergencies in patients with catastrophic diseases, such as heart disease, stroke, and kidney failure, is crucial for reducing mortality rates and improving the quality of care. The Early Warning Score (EWS) is a simple assessment method used to monitor vital signs and quickly identify potential emergencies. This community service program aims to educate the public, particularly patients' families, health cadres, and the general population, about the application of EWS. The activity involved 30 participants, utilizing a combination of material presentations, practical simulations, and evaluations through pre-tests and post-tests. The results showed an average increase in participants' knowledge of 30%, from a pre-test score of 55% to a post-test score of 85%. Furthermore, 90% of participants provided positive feedback regarding the benefits of this program. The education on EWS has proven effective in enhancing the community's preparedness for emergency situations and is expected to be implemented more widely to support healthcare services at the community level.